Determination of patients’ family members’ needs and related factors in the intensive care unit with visiting restrictions during the COVID-19 pandemic - KATRAN, HAMDİYE BANU (My University, 2022)
© 2022 Elsevier LtdObjectives: To determine the needs of family members of patients and related factors in the intensive care unit during the COVID-19 pandemic. Research methodology: This descriptive, cross-sectional, and correlational type study was conducted with a total of 301 family members. Data were collected by using two validated inquiry forms, the \"Introductory Information Form\" and the \"Critical Care Family Needs Inventory\" through an online survey. Descriptive statistical methods, as well as the Mann-Whitney U test, Kruskal-Wallis test, Dunn-Bonferroni test, and Backward Linear Regression Analysis, were used for the analysis of data. Results: The average scores of information, assurance, proximity, support, and comfort needs of family members were 3.54 ± 0.61 (Min = 1.11-Max = 4), 3.72 ± 0.60 (Min = 1-Max = 4), 3.50 ± 0.62 (Min = 1-Max = 4), 3.27 ± 0.77 (Min = 1.07-Max = 4), and 3.32 ± 0.73 (Min = 1-Max = 4), respectively. A very weak positive correlation was found between the ages of family members and information, assurance, and proximity needs (p < 0.05). Some variables such as sex, income level, and degree of affinity had significant effects on the needs of family members (p < 0.05). Conclusion: Family members of critically ill patients had needs at most in the assurance sub-dimension during the COVID-19 pandemic. As the length of time of family members spent in the hospital increased, their support and comfort sub-dimension needs also increased. Institutional policies should be developed to assure family members in intensive care units.
Keywords: Tıp; Hemşirelik; Sağlık Bilimleri; Medicine; Nursing; Health Sciences; Klinik Tıp (MED); Klinik Tıp; HEMŞİRELİK; Clinical Medicine (MED); CLINICAL MEDICINE; NURSING; Farmakoloji (hemşirelik); Onkoloji (hemşirelik); Asistan Hemşirelik; Tıbbi ve Cerrahi Hemşirelik; Annelik ve Ebelik; LPN ve LVN; Acil Tıp Hemşireliği; Yoğun Bakım Hemşireliği; İleri ve Uzman Hemşirelik; Hemşirelik (çeşitli); Genel Hemşirelik; Pharmacology (nursing); Oncology (nursing); Nurse Assisting; Medical and Surgical Nursing; Maternity and Midwifery; LPN and LVN; Emergency Nursing; Critical Care Nursing; Advanced and Specialized Nursing; Nursing (miscellaneous); General Nursing